PAI-1 modulates cell migration in a LRP1-dependent manner via β-catenin and ERK1/2 - Kozlova, Nina; Jensen, Jan K.; Franklin Chi, Tabughang; Samoylenko, Anatoly; Kietzmann, Thomas (Thrombosis and Haemostasis, 2015)
Plasminogen activator inhibitor-1 (PAI-1) is the major and most specific acting urokinase (uPA) and tissue plasminogen activator (tPA) inhibitor. Apart from its function in the fibrinolytic system, PAI-1 was also found to contribute to processes like tissue remodelling, angiogenesis, and tumour progression. However, the role of PAI-1 in those processes remains largely controversial with respect to the influence of PAI-1 on cell signalling pathways. Although PAI-1 does not possess its own cellular receptor, it can be bound to low-density lipoprotein receptor- related protein 1 (LRP1) which was proposed to modulate the β-catenin pathway. Therefore, we used wild-type mouse embryonic fibroblasts (MEFs), and MEFs deficient of LRP1 to study PAI-1 as modulator of the β-catenin pathway. We found that PAI-1 influences MEF proliferation and motility in a LRP1-dependent manner and that β-catenin is important for that response. In addition, expression of β-catenin and β-catenin-dependent transcriptional activity were induced by PAI-1 in wild type MEFs, but not in LRP1-deficient cells. Moreover, PAI-1-induced ERK1/2 activation was more prominent in the LRP1-deficient cells and interestingly knockdown of β-catenin abolished this effect. Together, the data of the current study show that PAI-1 can promote cell migration via LRP1-dependent activation of the β-catenin and ERK1/2 MAPK pathway which may be important in stage-specific treatment of human diseases associated with high PAI-1 levels.
Keywords: PAI-1; LRP1; beta-catenin; cell migration